Autoimmune Pancreatitis with Associated Ulcerative Colitis in a Teenager - Gouveia, CI (2018)
Autoimmune pancreatitis (AIP) is a rare entity that is extremely uncommon in children. Its diagnosis is also a clinical challenge. This form of chronic pancreatitis often presents itself with obstructive jaundice and/or a pancreatic mass and it is sometimes misdiagnosed as pancreatic cancer. We describe the case of a 13-year-old boy with obstructive jaundice and a 4 cm mass in the head of the pancreas that was diagnosed as AIP with associated ulcerative colitis.